Chromosome Analysis and Sorting Using Conventional Flow Cytometers. Issue 3 (15th March 2023) - Ng, Bee Ling
Abstract: The fluorescent dyes Hoechst (HO) and Chromomycin A3 (CA3) are commonly used for bivariate flow karyotyping to distinguish individual chromosomes from one another based on differences in base composition and DNA content. However, analysis of chromosomes using this fluorescent dye combination requires a flow cytometer equipped with lasers of specific wavelengths and higher power than is typical of conventional flow cytometers. This unit presents a chromosome staining technique with a dye combination of DAPI and propidium iodide (PI). Chromosomes stained using this dye combination can be analyzed on conventional flow cytometers equipped with a typical configuration of lasers and optics. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Cell culture and metaphase harvest of suspension cell line Alternate Protocol 1 : Cell culture and metaphase harvest of adherent cell line Basic Protocol 2 : Preparation of chromosome suspension using polyamine isolation buffer Basic Protocol 3 : Staining chromosomes with DAPI and propidium iodide Alternate Protocol 2 : Staining chromosomes with Hoechst and Chromomycin A3 Basic Protocol 4 : Bivariate flow karyotyping on a cell analyzer Basic Protocol 5 : Bivariate flow karyotyping on a cell sorter Basic Protocol 6 : Purification of flow‐sorted chromosomes